Palynology of the Last Interglacial Complex at Lake Ohrid: palaeoenvironmental and palaeoclimatic inferences - Sinopoli, Gaia; Masi, Alessia; Regattieri, Eleonora; Wagner, Bernd; Francke, Alexander; Peyron, Odile; Sadori, Laura (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this article, we present new, high-resolution, pollen results obtained from the DEEP site sequence recovered from Lake Ohrid (Albania/FYROM) for the Last Interglacial Complex (LIC), corresponding to Marine Isotope Stage 5 (MIS 5) of the marine isotope stratigraphy. LIC covers the period between 130 and 70 ka and includes the Eemian (Last Interglacial, LI) and the succession of stadial and interstadial phases of the Early Last Glacial. During the LIC, the pollen record shows an alternation of periods characterized by forest and open vegetation, clearly resembling the well-known vegetational succession of other European records. Our results reveal three key phases for the LI: a first period (128-125 ka) with a rapid increase in temperature and precipitation, a central phase (125-118.5 ka) characterized by a slight cooling, and a late phase (118.5-112 ka), with a decline both in temperatures and precipitation. Besides the LI, we identify four more forested periods dominated by mesophilous trees and intercalated by colder and drier steppe phases, during which, however, most arboreal taxa never disappear. During the Early Last Glacial we also identify several abrupt events that can be correlated to the succession of cold events recorded in the Greenland ice core records, associated to a weakening of the North Atlantic Meridional Overturning Circulation. The new high-resolution record indicates that Lake Ohrid is an important site to understand the response of vegetation to fluctuations in regional moisture availability and temperature changes, and thus provides new evidence for the connection between the Mediterranean Region and Northern Hemisphere climate oscillations. (C) 2017 Elsevier Ltd. All rights reserved.